Uric Acid Impairs Insulin Signaling by Promoting Enpp1 Binding to Insulin Receptor in Human Umbilical Vein Endothelial Cells - Tassone, Eliezer J.; Cimellaro, Antonio; Perticone, Maria; Hribal, Marta L.; Sciacqua, Angela; Andreozzi, Francesco; Sesti, Giorgio; Perticone, Francesco (Frontiers in Endocrinology, 2018)
High levels of uric acid are associated with type-2 diabetes and cardiovascular disease. Recent evidences attributed to uric acid a causative role in the appearance of diabetes and vascular damage. However, the molecular mechanisms by which uric acid induces these alterations have not been completely elucidated so far. Among the mechanisms underlying insulin resistance, it was reported the role of a trans-membrane glycoprotein, named either ectonucleotide pyrophosphatase/phosphodiesterase 1 (ENPP1) or plasma cell antigen 1 (PC-1), which is able to inhibit the function of insulin receptor (IR) and it is overexpressed in insulin resistant subjects. In keeping with this, we stimulated human umbilical vein endothelial cells (HUVECs) with insulin and uric acid to investigate the effects of uric acid on insulin signaling pathway, testing the hypothesis that uric acid can interfere with insulin signaling by the activation of ENPP1. Cultures of HUVECs were stimulated with insulin, uric acid and the urate transporter SLC22A12 (URAT1) inhibitor probenecid. Akt and endothelial nitric oxide synthase (eNOS) phosphorylation levels were investigated by immunoblotting. ENPP1 binding to IR and its tyrosine phosphorylation levels were tested by immunoprecipitation and immunoblotting. Uric acid inhibited insulin-induced Akt/eNOS axis. Moreover, uric acid induced ENPP1 binding to IR that resulted in an impairment of insulin signaling cascade. Probenecid reverted uric acid effects, suggesting that uric acid intracellular uptake is required for its action. In endothelial cells, uric acid directly interferes with insulin signaling pathway at receptor level, through ENPP1 recruitment. This evidence suggests a new molecular model of uric acid-induced insulin resistance and vascular damage.